2022
DOI: 10.1101/2022.02.21.480990
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Do we parse the background into separate streams in the cocktail party?

Abstract: In the cocktail party situation, people with normal hearing usually follow a single speaker among multiple concurrent ones. However, there is no agreement in the literature as to whether the background is segregated into multiple streams/speakers. The current study varied the number of concurrent speech streams and investigated target detection and memory for the contents of a target stream as well as the processing of distractors. A male-spoken target stream was either presented alone (single-speech), togethe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Event-related potentials measured at the Pz electrode are shown on Figure 2. The scalp distributions of the target N2 and P3 show maximal amplitude for both components over parietal scalp locations (Figure 3), as was also seen in our previous studies (Szalárdy et al, 2018(Szalárdy et al, , 2019(Szalárdy et al, , 2020a.…”
Section: Event-related Potential Measuressupporting
confidence: 87%
See 3 more Smart Citations
“…Event-related potentials measured at the Pz electrode are shown on Figure 2. The scalp distributions of the target N2 and P3 show maximal amplitude for both components over parietal scalp locations (Figure 3), as was also seen in our previous studies (Szalárdy et al, 2018(Szalárdy et al, , 2019(Szalárdy et al, , 2020a.…”
Section: Event-related Potential Measuressupporting
confidence: 87%
“…In a representative example, the mean difference was calculated between target and distractor events: the mean difference was 2.348 s (SD: 1.722 s, min: 0.013 s, max: 7.535 s). Distractor articles (but targets not) also contained 19-26 syntactic violations (M = 20.5, SD = 1.4), which served for control purposes, as Szalárdy et al, 2018Szalárdy et al, , 2020a found that when participants follow one of two concurrent speech streams, syntactic violations within the unattended stream do not elicit the syntax-violation related ERP components. Therefore, syntactic violations could be used to indicate whether the non-target stream(s) were attended or not.…”
Section: Stimulimentioning
confidence: 99%
See 2 more Smart Citations